Economic MPC with terminal cost and application to an oilsand primary separation vessel. (2nd November 2015) - Liu, Su; Zhang, Jing; Liu, Jinfeng
Abstract: In this work, a novel approach to construct the terminal cost for economic model predictive control (EMPC) is developed and two EMPC algorithms are designed based on the terminal cost for both infinite-time and finite-time operations. In the proposed approach, an auxiliary nonlinear controller which renders the desired optimal steady state asymptotically stable is taken advantage of. The idea is to take the auxiliary nonlinear controller as a benchmark control system and to design EMPC algorithms that gives practically better economic performance than the auxiliary nonlinear controller. The terminal cost ensures that the two EMPC algorithms give provable (practically) improved economic performance than the auxiliary controller with any prediction horizon. This means that the proposed EMPC algorithms could be very computationally efficient. The proposed EMPC algorithms are applied to an oilsand primary separation vessel. The simulation results demonstrate the effectiveness of the proposed approaches. Abstract : Highlights: A novel terminal cost construction method for EMPC. Two EMPC algorithms for both infinite-time and finite-time operations. Application to an oilsand separation vessel with extensive simulation results.